Elexacaftor/tezacaftor/ivacaftor improves chronic rhinosinusitis detected by magnetic resonance imaging in children with cystic fibrosis on long-term therapy with lumacaftor/ivacaftor - Wucherpfennig, Lena; Becker, Johanna K. Z.; Wünnemann, Felix; Eichinger, Monika; Seitz, Angelika; Baumann, Ingo; Stahl, Mirjam; Gräber, Simon Y.; Zhao, Shengkai; Chung, Jaehi; Schenk, Jens-Peter; Alrajab, Abdulsattar; et al. (Journal of cystic fibrosis, 2024)
Introduction: Previous studies using magnetic resonance imaging (MRI) demonstrated early onset and progression of chronic rhinosinusitis (CRS) from infancy to school age, and response to lumacaftor/ivacaftor (LUM/IVA) therapy in children with cystic fibrosis (CF). However, the effect of elexacaftor/tezacaftor/ivacaftor (ELX/TEZ/IVA) on CRS detected by MRI in children with CF and at least one F508del mutation, and potential incremental effects of ELX/TEZ/IVA compared to LUM/IVA in F508del homozygous children have not been studied. Methods: 30 children with CF with at least one F508del mutation underwent three longitudinal paranasal sinus MRI before (MRI1), without (n = 16) or with LUM/IVA therapy (n = 14, MRI2), and with ELX/TEZ/IVA therapy (MRI3, mean age at therapy initiation 11.1 ± 3.4y, range 6-16y). MRI were evaluated using the CRS-MRI score. Results: After therapy initiation with ELX/TEZ/IVA, the prevalence and in maxillary and sphenoid sinuses the dominance of mucopyoceles decreased (35% vs. 0 %, p<0.001 and 26% vs. 8 %, p < 0.05, respectively). This leads to a reduction in mucopyocele subscore (-3.4 ± 1.9, p < 0.001), and sinus subscores in MRI3 (maxillary sinus: -5.3 ± 3.1, p < 0.001, frontal sinus: -1.0 ± 1.9, p < 0.01, sphenoid subscore: -2.8 ± 3.5, p < 0.001, ethmoid sinus: -1.7 ± 1.9, p < 0.001). The CRS-MRI sum score decreased after therapy initiation with ELX/TEZ/IVA by -9.6 ± 5.5 score points (p < 0.001). The strength in reduction of mucopyoceles subscore and CRS-MRI sum score was independent of a pretreatment with LUM/IVA from MRI1-MRI2 (p = 0.275-0.999). Conclusions: ELX/TEZ/IVA therapy leads to improvement of CRS in eligible children with CF. Our data support the role of MRI for comprehensive monitoring of CRS disease severity and response to therapy in children with CF.
Online verfügbar: 13. Januar 2024, Artikelversion: 17. Mai 2024
Gesehen am 23.07.2025